2012
DOI: 10.1089/end.2012.0345
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Regional Hypothermia Using Transrectal Cooling During Radical Prostatectomy: Mitigation of Surgical Inflammatory Damage to Preserve Continence

Abstract: Preservation of continence and sexual function continues to be a formidable quality-of-life issue regarding outcomes after radical prostatectomy. There is little argument that physical preservation of the nerves and sphincters is a critical component to achieving success in these domains. Previously demonstrated factors such as advancing age, deteriorating physical health status, and subnormal baseline potency negatively impact outcomes. Our hypothesis, however, has been that inflammatory response to surgery h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Likewise, the same mechanism may be tested in a preprostatectomy cohort investigating urinary outcomes. Another evolving concept regarding reducing inflammation is hypothermia of the prostate via a rectal balloon at the time of surgery [16]. Our previous study is quite remarkable because all patients who received hypothermia during prostatectomy, had a significant reduction in post prostatectomy incontinence [17].…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, the same mechanism may be tested in a preprostatectomy cohort investigating urinary outcomes. Another evolving concept regarding reducing inflammation is hypothermia of the prostate via a rectal balloon at the time of surgery [16]. Our previous study is quite remarkable because all patients who received hypothermia during prostatectomy, had a significant reduction in post prostatectomy incontinence [17].…”
Section: Discussionmentioning
confidence: 93%
“…, who found that a cautery‐free nerve sparing improved early return of EF by 4.7‐fold. In the subsequent years, several studies confirmed the advantages of athermal dissection on EF outcomes .…”
Section: Ef Outcomes After Rarpmentioning
confidence: 85%
“…As thermal energy is considered a potential risk factor for nerve damage, application of hypothermia before dissection of the NVB has also been studied as a method to avoid tissue damage through decreased metabolic rate and oxygen demands . In a prospective study, Finley et al.…”
Section: Ef Outcomes After Rarpmentioning
confidence: 99%
“…The heat transfer fluid is circulated in closed-loop fashion through the catheter for the purpose of removing heat from the pelvic space. 4 To make the cooling system completely MR compatible several modifications were made including 1. An electrically isolated ECB thermistor removed, 2.…”
Section: Methodsmentioning
confidence: 99%
“…4 However measuring the point surface temperatures made by the thermal camera requires open surgery and is truly impractical: due to the bulky size of the camera and great difficulty for reliable and reproducible thermal photography of gradients especially laterally and ventrally. Preliminary studies by Chopra et al 5 in a study of tissue damage generated by heating of a laser induced hyperthermia on focal prostate cancer provided conceptual proof that MRI thermal mapping of the prostate is viable.…”
Section: Introductionmentioning
confidence: 99%